Technology Acceptance Model and E-Satisfaction in Mobile Banking - Putu Ayu Sinthia Adnyasuari; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2017)
ABSTRACTThis study aims to know how Bank BPD Bali customer’s accepted BPD Bali Mobile Application used Technology Acceptance Model’s theory. The study was conducted quantitatively and using a questionnaire as a tool in data collections. For statistical analysis and hypothesis testing using Structural Equation Modeling (SEM) and processing with AMOS version 22. Respondens in this study were customers of PT. Bank Pembangunan Daerah Bali Renon and Denpasar, taken a sample of 150 people by accidental sampling method.The results showed that construct of Technology Acceptance Model’s theory have positive effect. Perceived Ease of Use and Perceived of Usefulness have positive effect and significant on Attitude Toward Using dan E-Satisfaction. Attitude Toward Using have positive effect and significant on Actual System Usage.The management of PT. Bank Pembangunan Daerah Baliin order to improve the ability of employees in particular frontliner in providing explanations about mobile banking how to use, the existing of features and it’s benefit to customers, and adding mobile banking features to make customers feel easy, convenient, and secure in making transactions.